Bioaccumulation of Water Spinach (Ipomoea reptans Poir) in Phytoremediation of Heavy Metal Cu in Soil Contaminated by Lapindo Mud and Its Impact on Plant Growth - Zulfahnur Abi Abdillah; Purwadi; Moch Arifin (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Lapindo mud (LL) contains various heavy metals, including copper (Cu), with concentrations exceeding environmental quality standards, thereby posing a risk of soil and ecosystem contamination. One effective method to mitigate this pollution is phytoremediation using hyperaccumulator plants. This study aims to (1) assess the effect of mixing Lapindo mud with soil on Cu levels in the planting medium and (2) determine the optimal planting medium composition for Cu uptake by land spinach (Ipomoea reptans Poir). The experiment involved four planting medium treatments: 100% mud, soil:mud = 1:1, soil:mud = 1:2, and soil:mud = 1:3, each weighing 600 grams per polybag. Plants were harvested at 10 and 20 days after planting, and Cu levels in the soil and plants, bioaccumulation, and growth parameters such as plant height and dry weight were analyzed. Data were subjected to ANOVA at a 5% significance level, followed by the Least Significant Difference (LSD) test. Results indicated that mixing Lapindo mud with soil reduced Cu content in the planting medium, with the lowest Cu concentration in the 1:1 soil:mud treatment (25 ppm) and the highest in the 1:3 treatment (29 ppm). The 1:1 treatment also resulted in the highest Cu uptake (10.17 ppm) and a bioaccumulation index of 0.40, identifying it as the most effective composition for Cu phytoremediation. These findings highlight the potential of land spinach as a phytoremediator to reduce Cu pollution in soils contaminated with Lapindo mud.